Indigenous chicken production and marketing systems in Ethiopia: Characteristics and opportunities for market-oriented development - Moges, F.; Tegegne, Azage; Dessie, Tadelle (International Livestock Research Institute, 2010)
This working paper presents a synthesis of research findings undertaken in three woredas or districts (Bure, Fogera in Amhara Regional State and Dale in the Southern Nations, Nationalities and Peoples Regional State) in Ethiopia. These woredas are Pilot Learning Woredas (PLWs) of the Improving Productivity and Market Success (IPMS) of Ethiopian Farmers Project being implemented by the International Livestock Research Institute (ILRI). The major objective of these studies was to assess the existing indigenous chicken production and marketing systems and identify major constraints and priorities for improvement and extension interventions. A formal survey with structured questionnaire and Participatory Rural Appraisal (PRA) methods relevant to village chicken production systems were used to collect data. The result of these studies revealed that the dominant chicken production system of the study districts is an extensive/traditional type of production, using local chicken ecotypes, managed mainly on scavenging with seasonal feed supplementation of home-grown grains and household food refusals.